When cost efficiency is ignored, carbon market success is overstated - Xunpeng Shi; Jian Yu; Ke Wang; Peng Liu; Yi-Ming Wei (Nexus)
Understanding the true cost effectiveness of emissions trading schemes (ETSs) is essential for advancing climate policy. In this study, we contribute by introducing the trade effect—the mechanism through which ETSs promote convergence in marginal abatement costs (MACs)—and by developing a novel empirical framework to quantify this trade effect using firm-level data. Our empirical findings suggest that conventional assessments, which focus primarily on emissions reduction (the cap effect), may overstate the effectiveness of carbon markets by neglecting cost efficiency. Unlike earlier studies, our results reveal that China’s ETS, in its current form, has not consistently performed better than administrative measures in terms of cost effectiveness, indicating an insignificant trade effect. This divergence highlights a potential gap in current ETS evaluations and underscores the need for critical adjustments in China’s ETS, including stricter emissions caps, fewer free allowances, and a long-term strategic roadmap. Our approach provides a new lens for ETS performance evaluation, offering policymakers actionable insights to refine carbon market designs globally. Broader context: This research addresses the challenge of evaluating emissions trading schemes (ETSs) in achieving cost-effective climate policy. By focusing on the trade effect—the mechanism by which ETS drives convergence in marginal abatement costs among firms—this research reveals the limitations of conventional assessments that primarily emphasize emissions reduction of ETSs. The findings highlight a critical need for policy modification in China’s ETS, which could serve as a model for effective carbon market design worldwide. Longer term, the research aspires to improve carbon market structures, facilitating broader environmental goals at both the national and global levels, particularly in the context of international climate agreements. The interdisciplinary nature of this work integrates economics, environmental science, and public policy, fostering collaboration among diverse fields to enhance understanding of carbon market dynamics. Ultimately, effective ETS implementation can lead to significant societal benefits, including reduced emissions, lower abatement costs, and better alignment with global climate initiatives, supporting both China’s and the world’s transition to a sustainable future.